IMPLEMENTASI KONSEP NEW PUBLIC MANAGEMENT DI DINAS KOPERASI DAN UMKM KOTA SURABAYA - Sayidah, Nur; Mulyaningtyas, Alvy; Winedar, Mustika (JURNAL AKUNTANSI DAN AUDITING, 2015)
This article aims to determine the implementation of the concept of New Public Management (NPM) in the public sector, especially the Office of Cooperatives and SMEs Surabaya. Research approaches use qualitative. Method of data collection is done through interviews with heads of departments of Cooperatives and SMEs Surabaya. The data were analyzed by coding method. This method give the code on records that allow researchers to create a theme or concept through conceptual categorization. The results showed that the NPM concept is implemented in the Department of Cooperatives and SMEs Surabaya through measurement performance based on budget absorption and the benefit in society, creation of competition through competitive tender, valuation of individual performance based on remuneration system, and discipline and austerity in the use of resources